STRATEGI PENGEMBANGAN SARANA OBJEK WISATA TELABANG SAKTI DI KABUPATEN SIJUNJUNG - Waryono, Waryono; Suyuthie, Hijriyantomi; Ma’rufah, Utami (Journal of Home Economics and Tourism, 2017)
This research aims to describe the internal factors and external factors of the facilities development on the tourism object at Telabang Sakti and also to determine the development strategy of tourism facilities at Telabang Sakti. This research consists of three indicators of tourism facilities, namely: basic facilities, complimentary facilities and supporting facilities for tourism. The type of research is descriptive with qualitative data. Informans in this study are namely: 2 people from Dinas Pariwisata Kabupaten Sijunjung, 3 from managers attraction Telabang Sakti and 3 tourist attraction of Telabang Sakti. The development strategy of the facilities in the tourist attraction of Telabang Sakti are to increase the cooporeration of the government with the managers, renovate the resort in the tourist attraction, create a swimming pool with freshwater for snorkeling, increase the knowledge of food and drink merchants, add children’s playground, hold sports event calendar, while to the community to learn it is suggested how to make handicrafts, set a standard selling price, and more vigorous in looking for sponsors.Keywodrs: Strategy, Development, Facilities, SWOT Analysis1D4